Implementation of Tools in the Power Point Program for Arabic Books in Your Hand to Improve Learning Outcomes in Listening Skills for Preparatory Class “A” Students at Darusslam Gontor University Ponorogo - Ahmad Hidayatullah Zarkasyi; Arif Chasanul Muna (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Darussalam University Gontor is a university that requires students to speakarab and english in all activities. The university has a special class for studentswhose low language ability is the matriculation class. Arabic language learning inmatriculation class includes four skills, including: maharatul istima, maharatulkalam, maharatul qira'ah, and maharatul kitabah. This study aims to improve resultsof students on maharatul istima' lesson using power point media in arabiyah bainayadaik in the matriculation class A of Darussalam University Gontor. The object ofresearch is a student matriculation A University Darussalam Gontor whichamounted to 16 students. This type of research is a classroom action research(PTK). This classroom action research is collaborative, since researchers work withmaharatul istima 'teachers to teach in Matriculation class. This study has 2 cycles,and in each cycle there are four core components, including: planning,implementation, observation, and reflection. Data collection techniques used areobservation, interview, test and documentation. Data analysis technique used ismixed method analysis, that is approach with qualitative and quantitative. And thesuccess criteria in this study is 70%. The results of this study indicate that the powerpoint media can improve results of students on maharatul istima' lesson in thematriculation class A of Darussalam University Gontor. Data analysis on cycle Iproves as many as 12 students achieve the expected learning results with 75%complete percentage, and increased again in cycle II as many as 14 students achievethe expected learning results with 87,5% mastery percentage.